2021
DOI: 10.1029/2021jb022548
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Deformation and Fluids on Ti Exchange in Natural Quartz

Abstract: Using a combination of microstructural, spectroscopic, and geochemical analyses, we investigate how subgrain rotation recrystallization and fluid migration affect Ti concentration [Ti] in naturally deformed quartz veins from the Prijakt Nappe (Austroalpine Unit, Eastern Alps). These coarse‐grained quartz veins, that formed at amphibolite facies conditions, were overprinted by lower greenschist facies deformation to different degrees. During the overprint, subgrain rotation recrystallization was dominant during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…Grain boundary migration reset quartz towards the equilibrium Ti concentration for the recrystallization temperature. Volume diffusion of Ti through quartz is very slow [66,67], but strain-induced grain boundary migration can reset Ti in quartz towards a new equilibrium value at a rate that is much faster [68][69][70] especially in fluid-rich systems such as Butte [71]. Lower temperature recrystallization mechanisms-subgrain rotation and bulging recrystallization-can reset Ti to lower equilibrium values in certain conditions [71] but are generally much less likely to do so [71,72].…”
Section: Origin Of Cl-mottledmentioning
confidence: 99%
See 2 more Smart Citations
“…Grain boundary migration reset quartz towards the equilibrium Ti concentration for the recrystallization temperature. Volume diffusion of Ti through quartz is very slow [66,67], but strain-induced grain boundary migration can reset Ti in quartz towards a new equilibrium value at a rate that is much faster [68][69][70] especially in fluid-rich systems such as Butte [71]. Lower temperature recrystallization mechanisms-subgrain rotation and bulging recrystallization-can reset Ti to lower equilibrium values in certain conditions [71] but are generally much less likely to do so [71,72].…”
Section: Origin Of Cl-mottledmentioning
confidence: 99%
“…Volume diffusion of Ti through quartz is very slow [66,67], but strain-induced grain boundary migration can reset Ti in quartz towards a new equilibrium value at a rate that is much faster [68][69][70] especially in fluid-rich systems such as Butte [71]. Lower temperature recrystallization mechanisms-subgrain rotation and bulging recrystallization-can reset Ti to lower equilibrium values in certain conditions [71] but are generally much less likely to do so [71,72]. Haertel et al [73] found that synkinematic quartz veins that underwent retrograde bulging and subgrain rotation recrystallization during exhumation at temperatures less than 350 °C preserved Ti concentrations and gave thermometric estimates that were a close approximation of the temperature of original vein formation.…”
Section: Origin Of Cl-mottledmentioning
confidence: 99%
See 1 more Smart Citation
“…Total intensity CL maps show a lower intensity CL emission from the blue precipitated quartz. In recent studies on recrystallization of deformed quartz, decreased total CL intensity was linked to a reset of the Ti concentration in quartz 19 , 20 . Also in our samples we observe a decreased total CL intensity in the precipitated quartz with blue CL emission.…”
Section: Strain Accommodation and Deformation Mechanismsmentioning
confidence: 96%
“…Williams et al 18 used a cold-cathode CL system on a petrographic microscope to trace quartz precipitation in healed fractures and overgrowths after long duration quartz growth experiments (at 300–450 °C and 150 MPa, with an Al-enriched pore fluid containing amorphous silica). Recently, various authors used CL to visualize recrystallized quartz in experimentally and naturally deformed rocks, linking CL to trace element re-equilibration (especially Ti) resulting from the presence of grain boundary fluids during deformation, both at low and high temperatures 19 22 .…”
Section: Introductionmentioning
confidence: 99%